The short novels of John Steinbeck - Steinbeck, John, 1902-1968 (Penguin Books, 2009)
Collects six short novels from one of the most influential authors of the twentieth century
V tiráži: "Originally published: New York : Viking Press, 1953"
Keywords: americké povídky; American short stories